PEMAHAMAN JAMA’AH TABLIGH TENTANG UMMAT TERBAIK DALAM AL- QUR’AN SURAH ALI-IMRAN AYAT 110 - Achmad Ghozali Syafi'i; Sawaluddin Siregar; Dahliati Simanjuntak (Yayasan Baitul Hikmah al-Zain, 2025)
This study focuses on the understanding of the Tabligh congregation regarding the Qur'an Surah Ali Imran verse 110, which states that the best Muslims are those who carry out Allah's commands, preach, and invite to goodness and prevent evil. The method used in this study is a qualitative method with a field approach. Data were collected through in-depth interviews with several members of the Tabligh congregation, observations of the Tabligh congregation's preaching activities, and analysis of documents or literature used in the preaching process. The results of the study show that the Tabligh congregation understands the